2013
DOI: 10.1002/jctb.4138
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of pollutants removal from real sewage by embedding microbial fuel cell in anaerobic–anoxic–oxic wastewater treatment process

Abstract: BACKGROUND Developing an economical biological nitrogen and phosphorus removal technology with high efficiency has become a research priority in current sewage treatment procedures. In order to solve the problems within the anaerobic–anoxic–oxic (A2/O) process, including substrates competition and high energy consumption, a microbial fuel cell (MFC) was embedded in the A2/O process to enhance the efficiencies of removal of nitrogen and phosphorus, along with electricity production. RESULTS Three A2/O reactors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 36 publications
4
11
2
Order By: Relevance
“…However, the existing cheap cathode materials have low catalytic efficiency. Even if there are still some problems in the preliminary stage, the MFC has presented a promising technology for renewable energy production and still have some potential application, such as strengthening waste water treatment [28] , monitoring water quality [29] , and producing hydrogen [30] et al In the coming decades, MFC will involve more and more scientists and engineers who major in waste water treatment and energy production. …”
Section: Discussionmentioning
confidence: 99%
“…However, the existing cheap cathode materials have low catalytic efficiency. Even if there are still some problems in the preliminary stage, the MFC has presented a promising technology for renewable energy production and still have some potential application, such as strengthening waste water treatment [28] , monitoring water quality [29] , and producing hydrogen [30] et al In the coming decades, MFC will involve more and more scientists and engineers who major in waste water treatment and energy production. …”
Section: Discussionmentioning
confidence: 99%
“…With regard to municipal wastewater treatment, a study of integrating MFC into anaerobic/anoxic/oxic process (A 2 /O) has been reported (Xie et al, 2014b). It showed that the system can further improve the effluent quality.…”
Section: Othersmentioning
confidence: 99%
“…Lefebvre et al (2013) [18] reported high current density of 110 A/m 3 in an MXC from domestic wastewater, mainly due to high packing density of anodes in a small anode chamber (15 mL of working volume). In comparison, most of literature employing relatively large MXCs has commonly shown small current density from 0.4 to 43 A/m 3 for domestic wastewater [1], [9], [35], [36]. Feng et al [9] recently reported the maximum current density of 0.43 A/m 3 in a large-scale MXC (1 m 3 ), despite of using carbon brush anode, which implies the challenge of achieving high current density in large MXCs treating sewage.…”
Section: Introductionmentioning
confidence: 95%